2023
DOI: 10.1186/s12912-023-01395-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between workload and quality of work life of nurses taking care of patients with COVID-19

Abstract: Background The COVID-19 epidemic has brought significant changes and complexities to nurses’ working conditions. Given the crucial role of health workers, particularly nurses, in providing healthcare services, it is essential to determine the nurses’ workload, and its association with the quality of work life (QWL) during COVID-19 epidemic, and to explain the factors predicting their QWL. Methods A total of 250 nurses, who provided care for patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
1
5
0
1
Order By: Relevance
“…Our study found that the QWL of female nurses was at a moderate level, which is similar to previous studies in the UK ( 38 ), Iranian ( 20 ), and Canada ( 39 ), but higher than in Ghana ( 40 ). These similarities and differences across countries may be attributed to variations in cultural, social environments, healthcare systems, and nursing practices, which influence working conditions and subsequently affect nurses’ QWL.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study found that the QWL of female nurses was at a moderate level, which is similar to previous studies in the UK ( 38 ), Iranian ( 20 ), and Canada ( 39 ), but higher than in Ghana ( 40 ). These similarities and differences across countries may be attributed to variations in cultural, social environments, healthcare systems, and nursing practices, which influence working conditions and subsequently affect nurses’ QWL.…”
Section: Discussionsupporting
confidence: 90%
“…), as well as lifestyle and health-related factors (such as sleep quality, physical activity, menstruation status, etc.) which are well-known potential factors of depressive symptoms and QWL ( 20 , 21 ). Therefore, this study aimed to explore the effect of depressive symptoms on QWL in female nurses through PSM adjusting for confounding variables, which would provide inspiration for managers to developing mental health plans and psychological interventions for female nurses to improve mental health and QWL, then maintaining the nursing workforce.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in workload [ 67 , 68 ] and an increase in professional fulfillment [ 10 ], which was at a constant level in our collected data regardless of functional area, could represent possible targets for interventions that impose a high level of responsibility on the hospital as an employer [ 10 ]. Relating the strong association of workload and nurses’ quality of work life [ 69 ] to the findings of our study, new approaches to organizing work schedules and shifts could have significant implications for ward and OR nurses.…”
Section: Discussionmentioning
confidence: 67%
“…The safety precautions not only make them prioritize patient safety first but also make it imperative for them to cope with the obligations, workload, and demands of their professions by effectively balancing their work and spare time and protecting their health and overall life. 66 …”
Section: Discussionmentioning
confidence: 99%